Association Between COVID-19 Pregnant Women Symptoms Severity and Placental Morphologic Features - Rebutini, Patricia Zadorosnei; Zanchettin, Aline Cristina; Stonoga, Emanuele Therezinha Schueda; Prá, Daniele Margarita Marani; de Oliveira, André Luiz Parmegiani; Dezidério, Felipe da Silva; Fonseca, Aline Simoneti; Dagostini, Júlio César Honório; Hlatchuk, Elisa Carolina; Furuie, Isabella Naomi; Longo, Jessica da Silva; Cavalli, Bárbara Maria; et al. (Frontiers in Immunology, 2021)
Since the beginning of the pandemic, few papers describe the placenta's morphological and morphometrical features in SARS-CoV-2 positive pregnant women. Alterations such as low placental weight, accelerated villous maturation, decidual vasculopathy, infarcts, thrombosis of fetal placental vessels, and chronic histiocytic intervillositis (CHI) have been described. Objective: To analyze clinical data and the placental morphological and morphometric changes of pregnant women infected with SARS-CoV-2 (COVID-19 group) in comparison with the placentas of non-infected pregnant women, matched for maternal age and comorbidities, besides gestational age of delivery (Control group). Method: The patients in the COVID-19 and the Control group were matched for maternal age, gestational age, and comorbidities. The morphological analysis of placentas was performed using Amsterdam Placental Workshop Group Consensus Statement. The quantitative morphometric evaluation included perimeter, diameter, and number of tertiary villi, number of sprouts and knots, evaluation of deposition of villous fibrin, and deposition of intra-villous collagen I and III by Sirius Red. Additionally, Hofbauer cells (HC) were counted within villi by immunohistochemistry with CD68 marker. Results: Compared to controls, symptomatic women in the COVID-19 group were more likely to have at least one comorbidity, to evolve to preterm labor and infant death, and to have positive SARS-CoV-2 RNA testing in their concepts. Compared to controls, placentas in the COVID-19 group were more likely to show features of maternal and fetal vascular malperfusion. In the COVID-19 group, placentas of symptomatic women were more likely to show CHI. No significant results were found after morphometric analysis. Conclusion: Pregnant women with symptomatic SARS-CoV-2 infection, particularly with the severe course, are more likely to exhibit an adverse fetal outcome, with slightly more frequent histopathologic findings of maternal and fetal vascular malperfusion, and CHI. The morphometric changes found in the placentas of the COVID-19 group do not seem to be different from those observed in the Control group, as far as maternal age, gestational age, and comorbidities are paired. Only the deposition of villous fibrin could be more accentuated in the COVID-19 group (p = 0.08 borderline). The number of HC/villous evaluated with CD68 immunohistochemistry did not show a difference between both groups.